The influence of meteorological factors on the technical performance of football teams during matches - Zhong, Y.; Zhang, S.; Yi, Q.; Gómez Ruano, M. Á. (Biology of Sport, 2024)
This study explored the impact of the meteorological factors air temperature, relative humidity, and wind speed on teams` technical performance during the Union of European Football Associations Champions League (UCL). Technical match statistics were collected for five seasons (2016/2017-2020/2021). Thirty-one technical actions and events were categorized into three groups (goal scoring, offense, and defence). Meteorological data were collected from the official UEFA website (air temperature (°C): 11.59 ± 6.87, relative humidity (%): 71.40 ± 17.82, wind speed (km/h): 11.52 ± 7.02). LASSO regression analysis was employed to identify important indicators that affect match outcomes, while separate Poisson regression models were used in generalized linear modelling to determine the effects of meteorological factors on key technical performance indicators. The results revealed that offensive variables were instrumental in distinguishing match outcomes (winning, drawing, and losing), with meteorological factors significantly influencing these variables. Notably, "shot from counter attack" was the most significantly affected variable, being exclusively influenced by air temperature (OR = 0.55, 95% CI: 0.30 to 0.98). Two technical indicators, "dribbles won" and "shots from the 6-yard box," were both significantly influenced by two meteorological factors. "Cards per foul," an understudied variable, displayed a close association with all the three meteorological factors. These findings offer valuable insights for coaches and analysts in comprehending the influence of meteorological conditions on crucial technical variables during the performance evaluation of teams. Moreover, they provide valuable information to help coaches devise appropriate tactics for players before or during a match, considering the potential changes in meteorological conditions.